2016
DOI: 10.1590/s1984-82502016000300019
|View full text |Cite
|
Sign up to set email alerts
|

Chemical degradation kinetics of fibrates: bezafibrate, ciprofibrate and fenofibrate

Abstract: Fibrates are drugs used for the treatment of hypertriglyceridemia and for the prevention of atherosclerosis. Three drugs in the fibrate class, ciprofibrate, fenofibrate and bezafibrate, were chosen for this study because their raw materials are readily available and because scientific publications on these compounds is limited. To evaluate their intrinsic stability, the drugs were exposed to a test condition (temperature, oxidation, UV light exposure, hydrolysis at different pH values and metal ions in solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The hydrolysis of fenofibrate to fenofibric acid in the stomach had to the authors’ knowledge not been reported in vivo before. However, previous in vitro studies found significant instability of fenofibrate when a fenofibrate/methanol mixture was incubated with 0.1 M HCl for 4 h at 50 °C . The pH in the rat stomach has been found to be ranging from 1.9 ± 0.3 in the forestomach to 2.9 ± 0.7 in the glandular stomach, which supported that fenofibrate might be hydrolyzed into fenofibric acid by the acidic pH in the stomach in the current study.…”
Section: Resultssupporting
confidence: 85%
“…The hydrolysis of fenofibrate to fenofibric acid in the stomach had to the authors’ knowledge not been reported in vivo before. However, previous in vitro studies found significant instability of fenofibrate when a fenofibrate/methanol mixture was incubated with 0.1 M HCl for 4 h at 50 °C . The pH in the rat stomach has been found to be ranging from 1.9 ± 0.3 in the forestomach to 2.9 ± 0.7 in the glandular stomach, which supported that fenofibrate might be hydrolyzed into fenofibric acid by the acidic pH in the stomach in the current study.…”
Section: Resultssupporting
confidence: 85%
“…In our case, since the oxidant is in great excess, and it is practically not consumed, the reaction follows pseudo-first- Separations 2020, 7, x FOR PEER REVIEW 7 of 11 research using mass spectrometric detection intends to identify all oxidative by-products of GSH and to propose a stability-indicating method suitable for their quantification. The order of the oxidation reaction of GSH with H2O2 was evaluated by fitting three kinetic models, i.e., zero, first and second order [25]. As can be seen in Figures 5 and 6, using both HPLC and SI, the linearity was excellent for the first-order oxidation kinetics model (r > 0.99).…”
Section: Oxidative Forced Degradation Results and Kineticsmentioning
confidence: 92%
“…The order of the oxidation reaction of GSH with H 2 O 2 was evaluated by fitting three kinetic models, i.e., zero, first and second order [25]. As can be seen in Figures 5 and 6, using both HPLC and SI, the linearity was excellent for the first-order oxidation kinetics model (r > 0.99).…”
Section: Oxidative Forced Degradation Results and Kineticsmentioning
confidence: 93%
“…In pharmaceutical development, there is considerable interest in crystal structure investigations, as a way to understand how their structures (either amorphous or crystalline) and properties such as density, size, and particle shape correlate to other physicochemical properties, aiming the optimization of these drugs for solid dosage [ 5 ].…”
Section: Introductionmentioning
confidence: 99%